Molecular and physiological consequences of prematurity and blood pressure elevation on the young adult left ventricular stress response - Huckstep, O (2018)
Cardiovascular disease is the leading cause of global mortality. Acute disease usually strikes later in life, but risk trajectories are established earlier and are impacted by factors including preterm birth and blood pressure elevation. Prematurity results in increased left ventricular (LV) mass and is a risk factor for hypertensive disorders and heart failure later in life. Blood pressure elevation also contributes to increased LV mass and cardiovascular risk, and is increasingly prevalent in young adults. This thesis used purposive recruitment of young adults with a range of blood pressures and birth histories (preterm-born and term-born) and employed deep baseline cardiovascular phenotyping combined with exercise stress assessments to characterise LV stress response phenotypes in young adults born preterm, or with blood pressure elevation. Those born preterm were found to have impaired, declining exercise ejection fraction with increasing workload. This defect related to shorter LV length, a characteristic structural feature in the preterm-born. Preterm-born young adults also had a lower aerobic capacity than controls, which was commensurate with their exercise systolic impairment. In young adults with elevated blood pressure, it was found that submaximal exercise produced greater fatigue and impaired LV systolic performance vs normotensive controls. Blood pressure elevation was also associated with lower exercise capacity and enjoyment of physical activity and also sub-clinical LV mass increase. Collectively, these findings suggest preterm-born young adults have reduced myocardial functional reserve which likely contributes to risk of future disease including heart failure. Continued research is needed to better understand risk stratification and management for this population. In the blood pressure studies, the dysfunctional exercise stress response and lower aerobic capacity may indicate greater risk, while lower enjoyment of physical activity may confound exercise prescription. Future studies are needed to identify intervention strategies to optimally manage physiological and experiential challenges in this growing population.